Current Smoking Is Increased in Axial Psoriatic Arthritis and Radiographic Sacroiliitis - (:unkn) unknown (J RHEUMATOL PUBL CO, 2020)
Objective. The effect of smoking in psoriatic arthritis (PsA) is under debate. Our aim was to test whether smoking is increased in axial PsA (axPsA). Methods. Included in the analysis were 1535 patients from PsArt-ID (PsA-International Database). The effect of smoking on axPsA (compared to other PsA phenotypes) and radiographic sacroiliitis were investigated. Results. Current smoking was more common in axPsA (28.6% vs 18.9%, p < 0.001). It also was found as an independent predictor of axPsA (OR 1.4) and radiographic sacroiliitis (OR 6.6). Conclusion. Current smoking is significantly associated with both axPsA and radiographic sacroiliitis in patients with PsA.
Keywords: AXIAL PSORIATIC ARTHRITIS; SMOKING; SACROILIITIS; RISK-FACTORS; CIGARETTE-SMOKING; PROGRESSION; DAMAGE